Characterization of a heptapeptide‐modified microsphere for oriented antibody immobilization. (20th April 2022) - Bai, Shu; Zhang, Jie; Zhu, Liyan; Gong, Xiaoxing; Yu, Linling; Sun, Yan
Abstract : Oriented immobilization of antibodies is important for the effective recognition of target antigens. In this paper, a heptapeptide ligand, HWRGWVC (HC7), was modified onto non‐porous monosized poly(glyceryl methacrylate) (pGMA) microspheres (named pGMA‐HC7) to explore the antibody immobilization behaviors. Characterization of the microspheres by particle size analyzer, scanning electron microscopy, Fourier transform infrared spectroscopy, and reversed‐phase chromatography proved the success of each fabrication step. The capacity and activity of antibody immobilization through HC7 were studied using immunoglobulin G (IgG) as a model antibody and horseradish peroxidase (HRP) as a model antigen. Additionally, IgG immobilizations on pGMA microspheres by nonspecific adsorption and covalent coupling through carbodiimide chemistry were conducted for comparison. pGMA‐HC7 exhibited an IgG adsorption capacity of 3–4 mg/g in 10 min by the specific binding of HC7 without nonspecific interactions. Notably, the ligand HC7 showed a by two orders of magnitude stronger affinity for IgG than its original hexapeptide ligand HWRGWV. Moreover, the capacity and activity of the immobilized anti‐HRP antibody on pGMA‐HC7 were 1.6‐fold and 3‐fold higher than those of the covalent coupling, respectively. The results proved the superior role of HWRGWVC in the affinity binding of antibody and the potential of pGMA‐HC7‐25 in immunoassay and immunodiagnostic applications. Abstract : The heptapeptide ligand HWRGWVC showed much stronger affinity for IgG than its original hexapeptide ligand HWRGWV. The capacity and activity of the immobilized anti‐HRP antibody on HWRGWVC‐modified microspheres were 1.6‐ and 3‐fold higher than those of the covalent coupling, respectively, proving the potential of HWRGWVC‐modified microspheres in immunoassay and ‐diagnostic applications.